Vibration suppression of a micro beam subjected to magneto-electric load - Yıldırım, Kenan (Yildiz Technical Univ, 2021)
Control of vibrations, induced by magneto-electric load, by using piezoelectric actuator in a magneto-electroelastic micro beam is taken into account. Wellposedness and controllability properties of the system is discussed. Performance index functional to be minimized on control duration is chosen as a modified kinetic energy of the micro beam. By means of a maximum principle, optimal vibration control problem is transformed to a solving of a system of partial differential equations linked by terminal-initial-boundary conditions. Solutions are obtained by means of MATLAB and for indicating the effectiveness and robustness of the applied control actuation, results are presented in tables and graphical forms.
Keywords: Magneto-electric; Maximum principle; Micro beam; Vibration; Piezoelectric actuator; Wave-Propagation; Behavior